2009
DOI: 10.1073/pnas.0808400106
|View full text |Cite
|
Sign up to set email alerts
|

Selective induction of neocortical GABAergic neurons by the PDK1-Akt pathway through activation of Mash1

Abstract: GABAergic neuronal differentiation ͉ neural precursor cells ͉ telencephalon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 48 publications
5
57
3
1
Order By: Relevance
“…investigations showing that inhibition of 3-phosphoinositide-dependent protein kinase 1/Akt signaling reduces neurogenesis in neural progenitor cells, whereas constitutive activation of Akt or phosphatase and tensin homolog deletion promotes neurogenesis (Oishi et al, 2009;Gregorian et al, 2009). These results support the argument that FoxO negatively regulates neurogenesis in the brain.…”
Section: Foxos Play a Inhibitory Role In Neurogenesis And Synaptogenesissupporting
confidence: 78%
“…investigations showing that inhibition of 3-phosphoinositide-dependent protein kinase 1/Akt signaling reduces neurogenesis in neural progenitor cells, whereas constitutive activation of Akt or phosphatase and tensin homolog deletion promotes neurogenesis (Oishi et al, 2009;Gregorian et al, 2009). These results support the argument that FoxO negatively regulates neurogenesis in the brain.…”
Section: Foxos Play a Inhibitory Role In Neurogenesis And Synaptogenesissupporting
confidence: 78%
“…To examine the role of PDK1 in neocortical development, we first crossed mice harboring a floxed Pdpk1 allele (23) with those harboring a transgene for Cre recombinase under the control of a Nestin enhancer (24) to delete Pdpk1 in neural progenitor cells (NPCs) and their descendants throughout the CNS. We previously showed that PDK1 flox/flox ;Nestin-Cre mice die shortly after birth and have a reduced brain size (25). Immunohistofluorescence and immunoblot analyses confirmed that the abundance of PDK1 protein as well as the extent of Akt activation (as reflected by PDK1-mediated phosphorylation of Akt at Thr 308 or phosphorylation of Akt substrates with a typical Akt phosphorylation consensus sequence) were markedly reduced in the brains of such mice at postnatal day (P) 0 (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…The PDK1-Akt pathway contributes to the regulation of proliferation, survival, differentiation of, and metabolism in various cell types (22,25,36), but its role in neuronal migration has been unclear. We demonstrated a role for the PDK1-Akt pathway in neocortical neurons through the specific manipulation of postmitotic cells with the use of Nex Cre/+ mice or a Neurod1 promoterdependent Cre expression plasmid.…”
Section: Discussionmentioning
confidence: 99%
“…One common signaling pathway of EGF, FGF, and EPO is the phosphorylation of ERK1/2 through RAS and RAF kinases (Subramaniam and Unsicker, 2006). IGF1 signaling, on the other hand, leads to AKT phosphorylation by PI3K (Ye and D'Ercole, 2006), and AKT is involved in maintenance of neural precursor cells (Oishi et al, 2009). We hypothesized that LNK inhibits phosphorylation of ERK1/2 and AKT downstream of EGF, FGF, EPO, and IGF1 receptors.…”
Section: Lnk Suppresses Nspc Proliferation By Decreasing Growth Factomentioning
confidence: 99%